Effects of different interstock length on vegetative growth and flowering in peach cv. Pavie Catherine - Calderon Diaz, Facundo Javier; Weibel, Antonio Marcelo; Trentacoste, Eduardo Rafael (Elsevier, 2022)
Peach production needs appropriate management strategies to control canopy size, to increase tree density and yield, and to facilitate orchard operations. We evaluated compatibility, vegetative growth and flowering in peach trees cv. Pavie Catherine grafted on seven interstocks, at two interstock lengths (5 and 35 cm). Citation, Damas GF 1869, Hiawatha, Krymsk® 1, Monpol, MrS 2/5 and Myran were used as interstock. Rootstock for those interstocks was Monegro, which was used as a Control and also grafted on cv. Pavie Catherine but without interstock. The trial was carried out from 2017 to 2019 in Mendoza, Argentina, during the first three years of plantation establishment. The Hiawatha, Krymsk® 1 and Citation interstocks reduced in average 56% total shoot length, 33% shoot number per plant and 136% canopy volume compared to the Control. In contrast, interstocks Damas GF 1869, Monpol, MrS 2/5 and Myran showed similar vegetative growth to the Control. Among interstock treatments, the number and density of the flowers were 30% and 42% higher than the Control respectively. In the high grafted plants total shoot length, number of shoots and canopy volume decreased significantly, by 50%, 38% and 61% respectively, in relation to the low grafted ones. Reproductive characteristics followed a similar pattern, thus flowering shoot lengths were reduced in high than in low grafted plants and floral density increased in high grafted plants. In addition, bloom date was delayed in high grafted plants. Interstocks and interstock length influenced plant size significantly, providing an opportunity to increment tree density and improve canopy management.